Learning to Be Job Ready: Strategies for Greater Social Inclusion in Public Sector Employment - Bennett, A. J. W. (2011)
‘Learning to be job ready’ (L2BJR) was a pilot scheme involving 16 long-term unemployed people from a range of backgrounds being offered a 6-month paid placement within the care department of a city council in Northern England. The project was based on a partnership with the largest college in the city specialising in post-16 education and training for residents and employees. The college targeted people as potential candidates for the programme through their prior attendance on or interest in care courses at the college, rather than the council employing more traditional methods of recruitment. Surveys, focus groups and interviews were utilised to capture the views and experiences of the participants, project workers and line managers, and also evidence of the project’s impact on service delivery in the care department. The article adds to our conceptual and practical knowledge of corporate social responsibility (CSR) in the public sector in three distinct ways. From a social and business perspective, the findings of the research highlight a potentially more robust strategy for matching long-term unemployed citizens to training and job opportunities in the public sector than is otherwise possible through the more conventional route of the job centre. Secondly, through this approach and with appropriate pre-training, a greater understanding of and empathy for the service users can be developed in the new organisational members, strengthening the subsequent ethical delivery and quality of the service. Finally, a re-conceptualisation of Carroll’s influential model of CSR, which also specifically incorporates the ethical and social inclusion duties of public sector organisations not only as service providers but also as potential employers, offers a more tailored paradigm for understanding this unique yet under-researched element of CSR theory and practice.
Keywords: social care; Training and development; Disadvantaged communities; recruitment strategies; Social Inclusion; Equality; Public Sector; Corporate Social Responsibility